2020
DOI: 10.1016/j.gaitpost.2020.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Automated gait event detection for a variety of locomotion tasks using a novel gyroscope-based algorithm

Abstract: Background: The robust identification of initial contact (IC) and toe-off (TO) events is a vital task in mobile sensor-based gait analysis. Shank attached gyroscopes in combination with suitable algorithms for data processing can robustly and accurately complete this task for gait event detection. However, little research has considered gait detection algorithms that are applicable to different locomotion tasks. Research question: Does a gait event detection algorithm for various locomotion tasks provide compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 35 publications
(55 reference statements)
0
32
2
Order By: Relevance
“…As a first step, mid-swing phases were determined. It was shown that positive peaks of the angular velocity around the frontal axis denote the mid-swing phases of every step ( 29 31 ). Therefore, positive peak detection was used to determine the mid-swing phases of every gait cycle in the smoothed angular velocities around the participant's frontal axis.…”
Section: Methodsmentioning
confidence: 99%
“…As a first step, mid-swing phases were determined. It was shown that positive peaks of the angular velocity around the frontal axis denote the mid-swing phases of every step ( 29 31 ). Therefore, positive peak detection was used to determine the mid-swing phases of every gait cycle in the smoothed angular velocities around the participant's frontal axis.…”
Section: Methodsmentioning
confidence: 99%
“…Data in other studies has been segmented in a variety of ways including continuous walking [22], three gait cycles [21], or single gait cycles [26,27]. The higher-order data segmentation in those studies may prove to be clinically useful for use in a human activity recognition model that includes other activities (e.g., going up stairs or sit-to-stand), and integration with a gait event detection algorithm [55].…”
Section: Reducing the Burden For Cliniciansmentioning
confidence: 99%
“…Sarshar et al [26] who also used RNN to train two IMU sensors attached to the shanks, reported an accuracy of 0.9977 for both HS and TO events, however, they did not compute the error in prediction delays. Utilizing rule-based algorithms, Fadillioglu et al [27] presented an automated gait event detection method using a gyroscope attached to the right shank and reported an MAE of 7ms and 19ms for the HS and TO events respectively. More recently, Yu et al [28] also used a single sensor on the right foot with an LSTM-HMM hybrid model for gait event detection, reporting the accuracy only without mentioning the delays.…”
Section: Discussionmentioning
confidence: 99%